Analysis of the Effect of Profitability, Asset Structure, Liquidity, Sales Growth, and Company Size on the Capital Structure of State-Owned Companies Listed on the Indonesia Stock Exchange - Tamara, Angie; Elwisam; Digdowiseiso , Kumba (CV ODIS, 2023)
This study aims to analyze the effect of profitability, asset structure, liquidity, sales growth, and company size on the capital structure of state-owned companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The population in this study is all state-owned companies listed on the Indonesia Stock Exchange. The sample in this study was determined by purposive sampling based on the criteria obtained by samples from 16 state-owned companies. The data source used is secondary data with documentation methods using access to the IDX site. The analysis method used is multiple regression analysis using IBM SPSS 23. The results showed that the size of the company with proxies had a positive and significant effect, while the asset structure proxied with fixed asset ratio and liquidity proxied with current assets had a negative and significant influence, while profitability proxied with return on assets and sales growth proxied with growth did not influence the capital structure of state-owned companies listed on the stock exchange Indonesia period 2016-2020.